Influence of Machine Parameter Variation on Quantified PSOE in Feedforward Controlled PMSM - Maha Gamage, Ujala A.; Kuruppu, Sandun S. (IEEE Transportation Electrification Conference and Expo (Online), 2024)
Optimal torque generation of a permanent magnet synchronous machine (PMSM) is guaranteed through stator flux orientation with respect to the rotor flux using field-oriented control (FOC). In applications relying on a position sensor for proper FOC, the relative alignment between rotor zero position and sensor zero position needs to be calibrated (known as PSOE-Position Sensor Offset Error). However, fault conditions may subject the calibrated relative position sensor alignment to vary (either in a static or dynamic nature), leading to unexpected torque characteristics. PSOE quantification in general being reliant on motor parameters, and the variation of these motor parameters during operation is yet to be studied. This paper focuses on evaluating the influence of motor parameter variation on the quantified static PSOE in feedforward-FOC-controlled PMSMs. The research presented here further explores which parameters have more severe effect on quantified PSOE (in Feedforward FOC drives), along with strategies to eliminate the effect of parameter error during fault diagnosis.